First-line therapy for human cutaneous leishmaniasis in Peru using the TLR7 agonist imiquimod in combination with pentavalent antimony. - Cesar Miranda-Verastegui; Gianfranco Tulliano; Theresa W Gyorkos; Wessmark Calderon; Elham Rahme; Brian Ward; Maria Cruz; Alejandro Llanos-Cuentas; Greg Matlashewski (Public Library of Science (PLoS), 2009)
Background Current therapies for cutaneous leishmaniasis are limited by poor efficacy, long-term course of treatment, and the development of resistance. We evaluated if pentavalent antimony (an anti-parasitic drug) combined with imiquimod (an immunomodulator) was more effective than pentavalent antimony alone in patients who had not previously been treated. Methods A randomized double-blind clinical trial involving 80 cutaneous leishmaniasis patients was conducted in Peru. The study subjects were recruited in Lima and Cusco (20 experimental and 20 control subjects at each site). Experimental arm: Standard dose of pentavalent antimony plus 5% imiquimod cream applied to each lesion three times per week for 20 days. Control arm: Standard dose of pentavalent antimony plus placebo (vehicle cream) applied as above. The primary outcome was cure defined as complete re-epithelization with no inflammation assessed during the 12 months post-treatment period. Results Of the 80 subjects enrolled, 75 completed the study. The overall cure rate at the 12-month follow-up for the intention-to-treat analysis was 75% (30/40) in the experimental arm and 58% (23/40) in the control arm (p = 0.098). Subgroup analyses suggested that combination treatment benefits were most often observed at the Cusco site, where L. braziliensis is the prevalent species. Over the study period, only one adverse event (rash) was recorded, in the experimental arm. Conclusion The combination treatment of imiquimod plus pentavalent antimony performed better than placebo plus pentavalent antimony, but the difference was not statistically significant. Trial registration Clinical Trials.gov NCT00257530.